GANGGUAN MOTORIK PADA ANAK BERKEBUTUHAN KHUSUS: KAJIAN TENTANG DISPRAKSIA DAN CEREBRAL PALSY - Fuji Hastuti; Hijriati; Nohan Suharni; Dinda Azkia; Maya Rosita Urza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Motor disorders are one of the developmental impairments that can affect children's ability to perform movements, coordination, balance, and daily functional activities. In the context of special needs education, motor disorders not only impact physical functioning but also influence children's independence, learning participation, social interaction, and psychological development. This article aims to examine two types of motor disorders commonly discussed in special and inclusive education, namely dyspraxia and cerebral palsy. The study employed a library research approach by reviewing relevant theories and scientific literature in the fields of developmental psychology, special education, and child rehabilitation. The findings indicate that dyspraxia and cerebral palsy have distinct characteristics but both significantly affect gross motor skills, fine motor skills, coordination, and children's participation in educational and social environments. Dyspraxia is primarily associated with difficulties in motor planning and execution, whereas cerebral palsy is a neuromotor disorder resulting from brain injury or abnormalities during early brain development. The study further highlights the importance of understanding the characteristics and needs of children with motor disorders to support appropriate educational interventions and developmental assistance. Collaboration among teachers, parents, and professionals is essential to promote inclusive learning environments and optimize children's participation, independence, and overall quality of life.